Perlindungan Hukum dan Ham Terhadap Pekerja Perempuan di Malam Hari (Karaoke) di Kota Ambon - Barzah Latupono (SASI, 2012)
Morally required all states to respect, uphold and protect the rights of women. Oneform of women's rights is a guarantee to protect in accordance with religious values andhumanitarian as well as Pancasila and destination country listed in the 1945 Constitution. But until this moment women's right can't be applied to case of violance on women, especially in Maluku. The majority of women will not know their rights. Even if the female community, not many people demanding the fulfillment of these rights in the country. Enforcement of human rights especially women's Commercial Sex Workers must start from the parties involved in this work, ranging from the community around the site, pimps, Commercial Sex Workers themselves, government agencies such as the police, prosecutors, courts and social services